Pengaruh Metode Latihan Terhadap Kemampuan Dribbling Bola Dalam Permainan Sepak Bola Pada Siswa Ekstrakurikuler SMA Negeri 1 Puding Besar Kabupaten Bangka - Mutiara Fajar (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2019)
The problem in this study is the students' dribble ability of extracurricular football at SMA Negeri 1 Puding Besar is still very slow.The purpose of this study was to find out which exercises were better between Dogging Run exercises and Shuttle Run Exercises on students' dribble abilities. Extracurricular at SMA 1 Puding Besar Bangka Regency. The research method used is the Experimental research method. The data source of this research is 20 extracurricular football soccer extracurricular members of the Pudding Besar High School in Bangka Regency. The data analysis technique in this study used an independent test.The results of this study indicate that there is a significant effect of dogging run training on increasing the dribbling skills of extracurricular students at the 1 Puding Besar High School in Bangka Regency with a mean pretest of 11.96 seconds, posttest 10.66 seconds with a sig (2-tailed) value of 0.012 smaller than 0.025 seconds there was no significant effect of Shuttle run training on increasing ball dribbling skills of extracurricular students at SMA 1 Puding Besar Bangka Regency with mean pretest 12.88 seconds, post 13.00 seconds with sig (2-tailed) value 0.912 greater from 0.025. There was a significant difference between Dogging Run training and Shuttle Run training on improving ball dribbling skills in extracurricular students at SMA 1 Big Puding, Bangka Regency